Optical Properties of Pb:Doped Tellurite Glasses - ahmad, marzuki (2012)
Tell u rile glasses with molar co m posi tions of 55Te02-2Bi203-[43-x] ZnO-xPbO (in mol%) with x= I , 2, 3, 4, 5 have been fabricated and characterized. The optical absorption spectra were recorded at room temperature using UV VIS-NIR Spectrophotometer and FTIR while their refract i ve indices were determ i ned by the Orewster angl e method. It was observed that the glasses refractive index as well as their transm ittance range increase with the increase of PbO content Min i mum l oss of th e gl asses predicted from these spectroscopic data are situated between 2,31 ·I 0-JdB/m and 2,94·10-3 dB!m at wavelength around 5.5 tm